Response surface optimization of Curcuma zedoaria oil yield by SC-CO₂ extraction: article - Hisan, Nurul Nabilah; Subuki, Istikamah; Saidin, Saidatul Husni (2017)
With the increasing of public interest in natural or herbal products, the Supercritical Fluid Extraction (SFE) of Curcuma zedoaria (Berg.) Rosc. (Zingiberaceae) was study. Curcuma zedoaria was selected to be extracted due to its great potential in pharmaceutical. SFE technique was safe and time effective in extraction process. Although SFE was viable alternative, there was major drawback on this application which was the high capital and operating cost due to requirement of extreme pressure on the process. Besides, the operating parameter in SFE also will be give different effect on the extraction yields as well as oil component properties. Therefore, it was crucial to determine the optimum parameter used in SFE. The parameters used in SFE were pressure and temperature. The optimum parameters were determined by employing the Response Surface Methodology (RSM) based on the Central Composite Design (CCD). The Curcuma zedoaria was extracted by SFE with the pressure and temperature range between 100 to 300 bar and 40°C to 60°C respectively. The extracts or oil yield was collected, weighed and analyzed by using gas chromatography mass spectrometer (GCMS) and gas chromatography flame ionization detector (GCFID). Based on the results, most of the extraction of SFE gave oil yield ranged from 0.6% to 1.8%. For the analysis, curzerene concentration was found high at SFE 11 and low at SFE 8. Hence, the optimum parameter of Supercritical Carbon Dioxide (SC-CO₂) of Curcuma zedoaria at best oil yield and curzerene concentration obtained was 138.65 bar and 40°C. This optimum parameter gives the best predicted oil yield and curzerene concentration at 1.664 % and 3.696% respectively. In conclusion, the pressure and temperature significantly influence the oil yield as well as concentration of oil compounds.